2022
DOI: 10.1055/a-1995-6124
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-Catalysis-Enabled Ring-Opening Functionalization of Aryl Cyclopropanes

Abstract: Cyclopropanes have long been recognized as privileged synthons in organic synthesis to access 1,3-difunctionalized scaffolds. However, the synthetic potential of aryl cyclopropane, one of the most important subclasses of cyclopropanes, is far less explored. Recently, we uncovered a visible-light promoted strategy for the ring-opening functionalization of a series of aryl cyclopropanes through open-shell intermediates. By leveraging the activation of aryl radical cation derived from the oxidative single-electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Supported by the above-depicted control experiments, cyclic voltammetry results, and previous reports about the cyclopropane-derived radical cation, we proposed the reasonable reaction mechanism shown in Scheme . This four-component protocol begins with the direct anodic single electron oxidation of arylcyclopropanes 1a to deliver the key radical cation I , which is quickly captured by nucleophilic MeO – generated from the cathodic reduction of MeOH to produce benzyl radical intermediate II .…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Supported by the above-depicted control experiments, cyclic voltammetry results, and previous reports about the cyclopropane-derived radical cation, we proposed the reasonable reaction mechanism shown in Scheme . This four-component protocol begins with the direct anodic single electron oxidation of arylcyclopropanes 1a to deliver the key radical cation I , which is quickly captured by nucleophilic MeO – generated from the cathodic reduction of MeOH to produce benzyl radical intermediate II .…”
supporting
confidence: 67%
“…Among the established activation modes, the single-electron oxidation of arylcyclopropane to produce radical cations was proved to be feasible in the 1970s . Over the past few decades, numerous designed modular synthetic strategies for the single-electron oxidation of cyclopropanes by chemical and photochemical process have been developed (Scheme a). For instance, Studer et al achieved a radical-cation-mediated ring-opening 1,3-difunctionalization of arylcyclopropanes with acyl fluorides by merging NHC and organophotoredox catalysis in 2021 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 In 2016, Lectka's group reported a highly regioselective aminofluorination of aryl cyclopropanes using N -fluorobenzenesulfonimide (NFSI) as an N–F reagent via a photoredox-coupled reaction. 8 Notably, Feng and co-workers did very beautiful work on the photoredox-coupled ring-opening of cyclopropanes, 9 and they recently reported a photoredox-coupled ring-opening deoxygenation of aryl cyclopropanes for synthesizing 1,3/1,5-dioxygenation products. 10 Significantly, König's group reported a facile synthesis of β-chloro ketones via a visible light-mediated multicomponent cascade reaction of aryl cyclopropanes.…”
Section: Introductionmentioning
confidence: 99%
“…2 This strategy has also been successfully applied to the activation of aryl cyclopropanes, 3 refraining from using strong oxidants/electrophiles that were frequently utilized in earlier methods. 4 In 2019, our group reported an aerobic photoredox catalysed ring-opening 1,3-oxoamination of aryl cyclopropanes in which nitrogen-containing heterocycles functioned as nucleophiles (Scheme 1a). 5 Further mechanistic studies suggested that the aryl cyclopropane was first single-electron-oxidized by the excited photocatalyst to give an arylcyclopropane radical cation intermediate, which was predisposed to a regio- and stereospecific three-electron S N 2-like attack of a nitrogen-based nucleophile to produce a benzylic radical intermediate with the opening of the cyclopropane ring.…”
Section: Introductionmentioning
confidence: 99%